Advanced Glycation End Products are Increased in the Skin and Blood of Patients with Severe Psoriasis - Anastasia Papagrigoraki; Micol Del Giglio; Chiara Cosma; Martina Maurelli; Giampiero Girolomoni; Annunziata Lapolla (Medical Journals Sweden, 2017)
Psoriasis is frequently associated with metabolic comorbidities. Advanced glycation end products (AGEs) are highly oxidant, biologically active compounds that accumulate in tissues in association with hyperglycaemia, hyperlipidaemia and oxidative stress. This is a cross-sectional case-control study involving 80 patients with mild/severe psoriasis and 80 controls matched for age, sex and body mass index (40 with severe eczema, 40 healthy individuals). Patients and healthy individuals with a smoking habit, diabetes, dyslipidaemia, hypercholesterolaemia, hypertension or who were under systemic treatment were excluded from the study. Skin AGEs were measured in normal-appearing skin by a standard fluorescence technique, and blood AGEs (total AGEs, pentosidine and AGEs receptor) by enzyme-linked immunosorbent assay. Levels of cutaneous AGEs (p < 0.04), serum AGEs (p < 0.03) and pentosidine (p < 0.05) were higher in patients with severe psoriasis. Cutaneous AGEs correlated well with serum AGEs (r = 0.93, p < 0.0001) and with Psoriasis Area and Severity Index score (r = 0.91, p < 0.0001). Receptor levels were lower (p < 0.001) in severe psoriasis, and inversely correlated with disease severity (r = -0.71, p < 0.0002). Patients with severe psoriasis have accumulation of skin and serum AGEs, independent of associated metabolic disorders.